Learner-generated drawing as a learning strategy. The effect of teacher-guided intervention program “Learning with Understanding” on composing drawings in math word problems in the primary grades - Tolsberg, Kadri; Põldre, Siim; Kikas, Eve (Frontiers in Education, 2022)
The study aimed to examine the possibility of teaching primary school students a learner-generated drawing strategy, among other constructivist learning strategies. The teacher-guided program “Learning with Understanding” began by discussing the broader topics of the learning process, followed by teaching specific strategies, and ended with an overview of all strategies and reflective discussions. During 18 program lessons, primary school teachers taught, practiced, and raised metacognitive awareness of three learning strategies – elaboration of new information with familiar material and daily practice, organization of material into categories and elaboration, and organization of information through drawing. This study examined composing drawings for math word problems before and after the program. The sample consisted of second- and fourth-grade students from eight Estonian schools. The intervention group included 110 students from second grade and 80 students from fourth grade. The control group consisted of 121 second-grade students, and 82 fourth-grade students. Before and after the intervention, students had to solve two math word problems and compose a drawing, if needed. The results showed that before the intervention, neither the control group nor the intervention group students drew almost any drawings. However, after the intervention, both the control group and the intervention group students started to draw more drawings. Also, the intervention group students composed both more drawings and more schematic drawings. The effect of the intervention was visible at both grade levels. Comparing the correctness of answers with the drawing type showed that the fourth grade obtained significantly more correct answers when no drawings were made, while in the second grade, students had fewer correct answers when they had not compiled a drawing. Thus, we showed that even very young students could learn to compose schematic drawings; however, drawings alone may not be of help to solve the problem.